ANALISIS IMPLEMENTASI MUDHARABAH PADA BUDIDAYA IKAN LELE RAHMA FRAMS KELURAHAN DUREN SERIBU KOTA DEPOK - Abdus Salam; M. Kholil Nawawi, Hilman Hakiem (CV. Adiba Aisha Amira, 2025)
This research explores the application of the mudharabah contract, a profit- sharing partnership in which one party provides capital—either in the form of money or assets—while the other manages a specific business venture. The study adopts a qualitative approach with data gathered through fieldwork methods, including interviews, direct observations, and documentation. The key informants consist of managers and partners involved in catfish farming at Rahma Farm, located in Duren Seribu Village, where collaboration occurs between capital or pond owners and farm managers. SWOT analysis was employed to examine the internal and external factors influencing the partnership. Findings reveal that the profit-sharing agreement in this catfish farming practice is based on oral contracts, which lack legal enforceability. This arrangement is primarily driven by mutual trust and the intention to simplify the process of cooperation. The profit-sharing mechanism is carried out evenly, namely each party receives 50 percent of the business results. While the loss-sharing mechanism is borne entirely by the land owner.